2004
DOI: 10.1159/000078101
|View full text |Cite
|
Sign up to set email alerts
|

Mu Opioid Modulation of Oxytocin Secretion in Late Pregnant and Parturient Rats

Abstract: We have investigated effects of µ- and ĸ-opioid agonists and antagonists on plasma oxytocin levels and noradrenaline content in the supraoptic nucleus (SON) and paraventricular nucleus (PVN) of 20-day pregnant rats. β-Endorphin, oxytocin, estrogen and progesterone profiles in late pregnant and parturient rats were also sought. Stage of estrous cycle was monitored by vaginal smear, and pro-estrous animals were left overnight with male. In the first set of experiments, pregnant rats were monitored and decapitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 34 publications
1
20
0
4
Order By: Relevance
“…It has been reported that hypophysiotropic peptides such as thyrotropin-releasing hormone, gonadotropin-releasing hormone, corticotrophin-releasing hormone, and somatostatin are coexpressed with VGLUT2 (Hrabovszky et al, Hrabovszky et al, 2005a,b, 2006. Thus, our data suggest that activation of MOR 1C may modulate the release of some hypophysiotropic hormones (Plotsky, 1986;Doi et al, 2001;Kutlu et al, 2004).…”
Section: Hypothalamusmentioning
confidence: 61%
“…It has been reported that hypophysiotropic peptides such as thyrotropin-releasing hormone, gonadotropin-releasing hormone, corticotrophin-releasing hormone, and somatostatin are coexpressed with VGLUT2 (Hrabovszky et al, Hrabovszky et al, 2005a,b, 2006. Thus, our data suggest that activation of MOR 1C may modulate the release of some hypophysiotropic hormones (Plotsky, 1986;Doi et al, 2001;Kutlu et al, 2004).…”
Section: Hypothalamusmentioning
confidence: 61%
“…We hypothesize that oxytocin may be a good candidate. In vivo and in vitro studies have demonstrated that oxytocin is a potential prolactin-releasing factor [59, 60] Although it was suggested that oxytocin is not involved in the control of prolactin secretion at this time [57] because the antepartum prolactin surge was not inhibited by infusion of a specific oxytocin antagonist, we cannot rule out existing evidence that could support our hypothesis [61,62,63]. …”
Section: Discussionmentioning
confidence: 92%
“…When we studied the effect of the combined treatment of DAMGO with serotoninergic or GABAergic antagonists, a single time point was examined. Although our study suggests the participation of these neurotransmitters in the stimulation of prolactin release 30 min after DAMGO administration, we cannot exclude the possibility that other responses may have occurred at earlier or later time points, as for instance an indirect effect of (mu)receptor-mediated modulation of oxytocin secretion [78]. …”
Section: Discussionmentioning
confidence: 99%